Action learning, Leadership and Organizational Development in the Public Service - Hidayah, Ahmad (INDONESIAN JOURNAL OF SUSTAINABILITY, 2024)
An unprecedented investment is being made in leadership development across the public sector with the hope of increasing organizational capacity, and delivering the modernization and improvement of public services. Educational leadership programs are mushrooming and leadership development is a core theme of the organization's initiatives.In action learning activities have been attracting increasing interest as an approach that can simultaneously address individual and organizational development, in which learning is embedded in real and complex problems and people as social beings who all of them interact with others from diverse contexts or various points of view.Action learning, leadership and organizational development in public service exemplifies this action widely as a learning activity and considers evidence in the community to assess effectiveness as an approach to leadership development in general. With collections taken from all different public services, including Health, Licensing and other public services.This book describes various kinds of actions or ways of studying leadership in various organizations, such as social organizations, institutional organizations, health organizations and other organizations that are generally engaged in the public service sector in society in general. This book also explains in detail and details about the aspects and ways to lead a good and correct public service organization in accordance with the existing theory.Keyword : Learning, Leadership, Organizational, Public ServiceÂ